Peran Sumber Daya Manusia Dalam Proses Transformasi Organisasi Di Rumah Sakit - Vip Paramarta; Astria Apriliavini Priscila Palenewen; Harto Necsen Linelejan; Firdaus Firdaus; David Kolibu (Pusat Riset dan Inovasi Nasional, 2023)
Disruptive environmental changes make many organizations have no other choice but to transform. Forms of change that are incremental in nature such as improvements, innovations, and services. Hospitals need to make fundamental and radical changes in transformation. Hospitals are also required to carry out service transformations that enable patients to continue to receive health services. The purpose of this literature study is to find out more about the role of human resources in the organizational transformation process in hospitals. The method in this research is to study the literature. Literature study is used with data collection techniques by conducting a review study of books, literature, records, and reports that have something to do with the problem being solved. The results of the literature study that has been analyzed on the role of human resources in the process of organizational transformation in hospitals are optimizing capabilities, creating strategic vision and mission, giving trust in teams or organizations, and evaluating in terms of organizational vision and mission. It can be concluded that transformation is a process of adaptation to the existence of an organization. Organizational transformation at the hospital has also involved changes in organizational structure, cultural changes and the addition of types of hospital services. So that the transformation that is built through integrated and comprehensive service quality improvement activities with the implementation of hospital accreditation, which measures a number of performance indicators and evaluates hospital programs, guarantees the implementation of regulations, policies and standard operating procedures (SOPs) as a quality assurance effort. For Hospital Agencies this becomes a policy and a good process of change in increasing innovation, strategy and creating new things. Organizational transformation in human resource management into a change from a process that is planned and can be managed.